Science and spectacle in the European Enlightenment - Bensaude-Vincent, Bernadette 1949-; Blondel, Christine (Science, Technology and Culture, 1700-1945, 2016)
Introduction: A Science Full of Shocks, Sparks and Smells -- 1 The Laboratory, the Workshop, and the Theatre of Experiment -- 2 Technology, Curiosity and Utility in France and in England in the Eighteenth Century -- 3 Amusing Physics -- 4 Experimental Physics in Enlightenment Paris: The Practice of Popularization in Urban Culture -- 5 Domestic Spectacles: Electrical Instruments between Business and Conversation